Empowerment of Women in the Making of Multi-Nutritional Instant Mulve from Local Food (Jalar, Corn, Ubi Leaves, Banana Heart, and Mujair Fish) To Overcome Stunting in Sitiotio, Samosir District - Aritonang, Evawany; Sarumpaet, Sori Muda; Syarifah; Halinda (Talenta Publisher, 2021)
Stunting is a chronic nutritional problem in toddlers characterized by a shorter height compared to other children of their age. Monitoring Nutritional Status (PSG) in North Sumatra Province in 2017, the prevalence of stunting in Samosir Regency was 33.1%. A preliminary survey by the community service team in Sitiotio District found that there is a desire of the community to tackle stunting by using local foods. The aim of the first year service is to empower mothers to overcome stunting problems through the production of nutrient-rich instant porridge for toddlers. The implementation of the first year service was carried out by introducing local food which is used for making instant porridge. The practice of making instant porridge was responded well by PKK women, posyandu cadres, the Samosir health office, and the head of the Sitio-tio puskesmas. The dedication team provides equipment that supports the production of nutritious food, namely large capacity ovens and high speed dry matter blenders. It is hoped that learning about instant porridge production with local food can be applied by the people of Sitio-tio village so as to reduce the prevalence of toddler stunting in Samosir district in the coming year.